Bovine in vitro Embryo Production: State of the Art - F. Gallegos; A. Mancheno; L. Mena; A. Murillo (ESPOCH Congresses, 2022)
Abstract In the last 10 years, bovine in vitro embryo production has shown significant progress on a global level, partly driven by a better understanding of technology potential in the livestock sector. Importantly, in 2016, the number of viable bovine embryos produced in vitro exceeded the number of transferable embryos derived in vivo (multiple ovulation embryo transfer, MOET). In vitro embryo production (PIVE) requires the correct formulation of culture media to allow the development of oocytes and embryos. In cattle, the PIVE process includes three sequential processes in vitro: maturation of oocytes, fertilization of matured oocytes, and culture of fertilized oocytes to obtain embryo development of blastocyst. In vitro-produced blastocysts can be transferred fresh to synchronized recipients or be cryopreserved (vitrified or frozen) for later transfer or commercialization. These assisted reproduction techniques have demonstrated acceptable outcomes in livestock, helping technicians and farmers to improve reproductive performance, production efficiency, and genetic progress.